PERANCANGAN APLIKASI WEB E-TICKETING IT SUPPORT BERBASIS WEBSITE (Studi Kasus PT. Swadharma Duta Data) - Ichsan Kurniawan; Niki Ratama (Journal of Research and Publication Innovation, 2024)
The use of computer applications encourages the formation of an e-ticketing helpdesk application that is able to accommodate activities and problems that may occur at any time in activities that occur in a company, especially the IT Support division. Generally, when accessing services using a device, there may be interference and damage that we don't want. The main factors in the problems that occur in this company start from arranging the handling of damaged assets, such as: PCs, troubleshooting, printers, etc.) which takes days because quite a few complaints are reported to carrying out the handling process. The aim of the research is to resolve complaints regarding several damaged devices if repairs are needed so that they proceed optimally from the start of submitting the application and then confirming the signature for approval when handling the problem (problem) by building a web-based system application. The analytical method technique used in this research is PIECES analysis in evaluating the problem being researched. The results of the system created do not take days and reported complaints can be immediately handled according to the features contained in the system regarding reports on a high, medium and low priority scale.